2015
DOI: 10.1039/c5fd90015h
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal resolution of primary processes of photosynthesis

Abstract: Technical progress in laser-sources and detectors has allowed the temporal and spatial resolution of chemical reactions down to femtoseconds and Å-units. In photon-excitable systems the key to chemical kinetics, trajectories across the vibrational saddle landscape, are experimentally accessible. Simple and thus well-defined chemical compounds are preferred objects for calibrating new methodologies and carving out paradigms of chemical dynamics, as shown in several contributions to this Faraday Discussion. Aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 112 publications
(200 reference statements)
0
1
0
Order By: Relevance
“…The oxygen-evolving center (OEC) of photosystem II (PSII) is a unique biological catalyst that catalyzes the watersplitting reaction at ambient temperatures and pressures, to release protons, electrons, and dioxygen molecules. [1] Crystallographic studies of PSII [2] have revealed that OEC is composed of one Mn 3 CaO 4 cubane attached by a "dangler" manganese via two bridging oxides, forming an asymmetric Mn 4 CaO 5 cluster (Figure 1 A,B). Its peripheral ligands are provided by four water molecules, one imidazole and six carboxylate groups of amino acid residues in PSII.…”
mentioning
confidence: 99%
“…The oxygen-evolving center (OEC) of photosystem II (PSII) is a unique biological catalyst that catalyzes the watersplitting reaction at ambient temperatures and pressures, to release protons, electrons, and dioxygen molecules. [1] Crystallographic studies of PSII [2] have revealed that OEC is composed of one Mn 3 CaO 4 cubane attached by a "dangler" manganese via two bridging oxides, forming an asymmetric Mn 4 CaO 5 cluster (Figure 1 A,B). Its peripheral ligands are provided by four water molecules, one imidazole and six carboxylate groups of amino acid residues in PSII.…”
mentioning
confidence: 99%